Faktor-Faktor yang Berhubungan dengan Kejadian Dismenore pada Remaja Putri di MTs Rabiatul Adawiyah Baturaja Kabupaten Oku Tahun 2025 - Wulandari Wulandari; Eka Rahmawati; Arie Anggraini (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
The Sustainable Development Goals (SDGs) are a global development agenda for the period 2016 to 2030, continuing from the MDGs. The fifth goal of theSDGs is to empower all women and girls, particularly in improving women's reproductive health (Selia Desma Sari et al., 2024). According to the World Health Organization, it is estimated that the number of women experiencing severe dysmenorrhea globally is 1,769,425 individuals (90%), with 10–15% experiencing mild dysmenorrhea. This study aims to determine the relationship between the level of knowledge, stress levels, and fast food consumption with the incidence of dysmenorrhea among adolescent girls at MTs Rabiatul Adawiyah Baturaja in 2025. Theresearch was conducted in August at MTs Rabiatul Adawiyah Baturaja. This is a cross-sectional study with a population of 70 respondents and a sample of 41 respondents selected using stratified random sampling. The type of data used is primary data collected through interviews, and the instrument used was a questionnaire. Data analysis was performed using the chi-square statistical test with a p-value ≤ α (0.05). The results showed that 26 respondents (63.4%) with poor knowledge levels experienced dysmenorrhea (p-value = 0.002). Among 31 respondents experiencing stress, 30 (73.2%) had dysmenorrhea (p-value = 0.001). Meanwhile, of the 29 respondents who frequently consumed fast food, 28 (68.3%) experienced dysmenorrhea (p-value = 0.000).It can be concluded that there is a significant relationship between the level of knowledge, stress level, and fast food consumption with the incidence of dysmenorrhea among adolescent girls at MTs Rabiatul Adawiyah Baturaja in 2025.